Audit Operasional, Pengendalian Internal, dan Manajemen Pergudangan: Studi Pada Toserba Yogya - Anugrah, Elsa Cintia; Tugiman, Hiro; Triyanto, Dedik Nur (Esensi: Jurnal Bisnis dan Manajemen, 2017)
Operational Audit, Internal Audit and Inventory Management: Study at Toserba YogyaIn a trading company, inventory is an asset that needs to be managed properly. The objective of this study is to determine the influence of operational audit and internal control on warehouse management of Yogya Mitrabatik department store Tasikmalaya. This study is using descriptive and multiple linear regression analysis method. Sample of the study are 50 employees whoinvolved in the warehouse management and internal auditors.The study found that all of the variables have been implemented well. The operational audit and internal control influence the warehouse management significantly and simultaneously with 0.337 determination coefficient score. While partially, only internal control that significantly and positively influence on the warehouse management. This research implies that the store should increase the control of their inventory.DOI: 10.15408/ess.v7i2.5208